KUALITAS HASIL BELAJAR STATISTIKA SISWA MTs YANG DIBELAJARKAN DENGAN PENDEKATAN PROBLEM POSING - Nuralam Nuralam Nuralam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
High and low acquisition of students' mathematics learning outcomes is influenced by internal and external factors. External factors of concern are related learning approaches so students are easy to learn mathematics. There is a tendency for the role of students to be more passive and teachers to be more active in the process of learning mathematics. This condition results in low acquisition of mathematics learning outcomes. One alternative solution is to teach students through the problem posing approach, so as to contribute to the involvement of students in learning mathematics. The purpose of this study was to find out: (1) statistics learning outcomes of students taught through the problem posing approach were higher than those taught through direct learning approaches and (2) student responses after the statistical learning process with a problem posing approach. This study uses a quasi-experimental study with a control group only design post test design. The population is students of MTsS Darul Hikmah Aceh Besar grade VIII and the sample was total sampling. Data were collected by statistical learning outcomes and response questionnaires. Data analysis techniques used t test for test data and response questionnaire data through analysis of average score criteria. Based on the results of the analysis of the test data obtained that tcount >ttable is 2,45 > 1,70. From the results of the questionnaire data the average score was 3.29. It was concluded that the statistical learning outcomes of students taught through the problem posing approach were higher than those taught through direct learning approaches. And the student response questionnaire after the statistical learning process with the problem posing approach in the very positive category